A Turning Point in Gender Bias in Mortality? An Update on the Number of 'Missing Women' - Stephan Klasen; Claudia Wink (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2001)
More than 10 years ago, Amartya Sen estimated than some 100 million women are 'missing' as a result of excess female mortality in parts of the developing world, most notably South Asia, China, West Asia, and parts of North Africa (Sen, 1989; Sen 1990). Coale (1991) and Klasen (1994) used more precise demographic techniques and arrived at figures that varied between 60 million (Coale) and 90 million (Klasen). All three estimates confirmed the enormous toll excess female mortality was exacting on women in these parts of the world. All these estimates 'missing women' were based on demographic information of the 1980s and early 1990s. Since then, there has been considerable speculation about current trends of gender bias in mortality with some observers suggesting a falling intensity while others predicted the opposite (e.g. Klasen, 1994; Das Gupta and Mari Bath, 1997; Dreze and Sen, 1995; Mayer, 1999; Croll, 2000). Figure 1 shows recent projections by the United Nations Population Division of the sex ratio in the world and in the regions where males outnumber females. These estimates suggest that the sex ratio in the female deficit regions, after rising steadily since 1960, is estimated to peak in about 1985 and then are believed to decline quite sharply. Given the high share these regions have in the world's total population, a turning point in the global sex ratio, after a similar rise since 1960, is also estimated for 1995.
urn:nbn:de:bvb:19-epub-23-5
Keywords: D63; J7; J16; 330